2016
DOI: 10.1039/c6ra10176c
|View full text |Cite
|
Sign up to set email alerts
|

PdSn nanocatalysts supported on carbon nanotubes synthesized in deep eutectic solvents with high activity for formic acid electrooxidation

Abstract: Deep eutectic solvents (DESs) are being increasingly used in electrochemically controllable synthesis of functional nanomaterials because of their unique merits (e.g., high conductivity, wide electrochemical windows and environmental friendship). Herein, we report a novel strategy in DESs for the fabrication of multi-walled carbon nanotubes (MWCNTs)-supported Pd-based alloy nanostructures. Using a NaBH 4 solvothermal reduction process in DESs, highly active PdSn alloy nanocatalysts supported on MWCNTs towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The intense decay in current density because of the production and adsorption of intermediate carbonaceous species on the catalysts surface goes along with the block of active sites as well as poisoning of catalysts surface. [30][31][32][33][34][35][36][37][38][39][40] Aer an early intense drop in performance, the current densities were stabilized at 5.2 and 45.6 mA cm À2 for Pd/C and Pd-Cu aerogel, respectively. The very high catalytic activity and durability of the Pd-Cu aerogel than that of Pd/C are attributed to the two vital reasons: (1) the presence of abundant open pores as well as easy access to large active sites of Pd-Cu aerogel, and (2) the selfsupporting property of the Pd-Cu aerogel, which may hinder the loss of stability observed in Pd supported on carbon owing to corrosion.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…The intense decay in current density because of the production and adsorption of intermediate carbonaceous species on the catalysts surface goes along with the block of active sites as well as poisoning of catalysts surface. [30][31][32][33][34][35][36][37][38][39][40] Aer an early intense drop in performance, the current densities were stabilized at 5.2 and 45.6 mA cm À2 for Pd/C and Pd-Cu aerogel, respectively. The very high catalytic activity and durability of the Pd-Cu aerogel than that of Pd/C are attributed to the two vital reasons: (1) the presence of abundant open pores as well as easy access to large active sites of Pd-Cu aerogel, and (2) the selfsupporting property of the Pd-Cu aerogel, which may hinder the loss of stability observed in Pd supported on carbon owing to corrosion.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…However, a limitation of the shaped NPs is their morphological instability. , It has been reported that monometallic Pd catalysts deactivate and degrade by dissolution of Pd under acidic operation conditions, ,, and, thus, the preservation and optimization of the activity and stability of the catalyst is of crucial interest. Therefore, the addition of a second metal, such as Au, , Pt, Ag, Ti, Pb, Fe, or Sn, ,, provides a common strategy for enhancing the activity and stability of Pd-based catalysts. Most known Pd-M catalysts form alloys, which not only lead to a variation of the reaction mechanism, but also generally improve the stability …”
Section: Introductionmentioning
confidence: 99%
“…It improves the electrocatalytic activity and stability of the PdSn–MNT/C. 42 The synergetic effect of binary metal catalyst produces higher peak current density for the PdSN–MNT/C electrode. This experiment is in good accord with the published literature on other metal oxides promoted for the MOR.…”
Section: Resultsmentioning
confidence: 99%